Molar-incisor hypomineralisation (MIH) - Cheong, Joo Ming (Child Dental Health Department, Bristol Dental School, University of Bristol, 2018)
Definition, aetiology, prevalence, types, clinical presentation, possible problems, differential diagnosis and treatment options of molar-incisor hypomineralisation (MIH) were described.